Hubungan Tingkat Pengetahuan dan Sikap Masyarakat dalam Pencegahan Covid-19 - Rini Ekasari; Indah Puspita Sari; Maratun Shoaliha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
SARS-CoV-2, the cause of the COVID-19 pandemic, first appeared in Wuhan, China. Based on the clinical and epidemiological impact, there is an increase in transmission, virulence, and the ability to evade immunity formed by vaccination. The COVID-19 prevention activities include the application of wearing masks, washing hands, keeping a distance, and staying at home. To determine the relationship between the level of knowledge and public attitudes in preventing COVID-19 in RW 013, Pasir Angin Village, Cileungsi. This study uses a descriptive method with a cross-sectional approach with a purposive sampling technique through filling out a questionnaire—analysis of the data used in univariate and bivariate. The study results obtained 96 respondents with 35.4% male respondents and 64.6% female respondents, indicating that the level of knowledge is 92.7%, a good attitude is 87%. Based on the research conducted, there is a relationship between the level of knowledge and attitude p-value = 0.001, more diminutive than 0.05. As for the Confidence Interval value of (3.901 - 128.622). From the study results, it was concluded that the community in RW 013 Pasir Angin Village Cileungsi had good knowledge of 92.7% and attitudes in the good category of 87%. Relationship between the level of knowledge and community attitudes in preventing COVID-19 in RW 013 Pasir Angin Village, Cileungsi, with a p-value of 0.001, smaller than 0.05 for the Confidence Interval value of (3.901 - 128.622).